2011
DOI: 10.3727/096368910x516592
|View full text |Cite
|
Sign up to set email alerts
|

MAPC Transplantation Confers a more Durable Benefit than AC133+Cell Transplantation in Severe Hind Limb Ischemia

Abstract: There is a need for comparative studies to determine which cell types are better candidates to remedy ischemia. Here, we compared human AC133+ cells and multipotent adult progenitor cells (hMAPC) in a mouse model reminiscent of critical limb ischemia. hMAPC or hAC133+ cell transplantation induced a significant improvement in tissue perfusion (measured by microPET) 15 days posttransplantation compared to controls. This improvement persisted for 30 days in hMAPC-treated but not in hAC133 + -injected animals. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…One of the major therapeutic effects of cell therapy in stroke is the support of the cells to angiogenesis, in part due to the upregulation of angiogenic growth factors and receptors, such as VEGF, VEGFR and angiopoietins [5]. In the current study, we did not examine the production of angiogenic growth factors from MSCs or MAPCs but as previously shown, both human and mouse MAPCs produce significant amounts of VEGF, PlGF, bFGF, PDGF-BB and even TGF-β, all of which are implicated in angio-vasculogenesis [50], [51]. We hypothesize that higher levels of these growth factors in hMAPCs versus hMSCs could explain the greater effect observed in animals treated with hMAPCs.…”
Section: Discussionmentioning
confidence: 83%
“…One of the major therapeutic effects of cell therapy in stroke is the support of the cells to angiogenesis, in part due to the upregulation of angiogenic growth factors and receptors, such as VEGF, VEGFR and angiopoietins [5]. In the current study, we did not examine the production of angiogenic growth factors from MSCs or MAPCs but as previously shown, both human and mouse MAPCs produce significant amounts of VEGF, PlGF, bFGF, PDGF-BB and even TGF-β, all of which are implicated in angio-vasculogenesis [50], [51]. We hypothesize that higher levels of these growth factors in hMAPCs versus hMSCs could explain the greater effect observed in animals treated with hMAPCs.…”
Section: Discussionmentioning
confidence: 83%
“…MAPCs were isolated from bone marrow, clonally purified and well‐characterized multipotent cells with differentiation potential into a variety of cell lineages including endothelial cells, smooth muscle cells, neurons, hepatocytes and cardiac myocytes . MAPCs promote angiogenesis and improve cardiac and limb function when injected into the peri‐infarct areas in ischaemic mice . These cells have extensive replication potential, are commercially available at clinical grade (Athersys Inc, Cleveland, Ohio) and are non‐immunogenic for alloreactive cytotoxic T lymphocyte induction, thus without potential adverse immune reactions .…”
Section: Discussionmentioning
confidence: 99%
“…The MultiStem clinical product is based on MAPC isolation and expansion protocols (Boozer et al, 2009). Pre-clinical animal studies have clearly shown therapeutic benefits of MAPC/MultiStem cells by preventing GvHD (Kovacsovics-Bankowski et al, 2009), and improving tissue regeneration and function in cardiovascular and neurological disorders, including acute myocardial infarct, traumatic brain injury, spinal cord injury, and ischemic limb injury (van’t Hof et al, 2007; Aranguren et al, 2008, 2011; Mays et al, 2010; Walker et al, 2010, 2012; Busch et al, 2011a). …”
Section: Multistem Cellsmentioning
confidence: 99%
“…The therapeutic benefits of MAPC are multimodulatory and have been shown to be caused, at least in part, by their pro-angiogenic effect through trophic support (Aranguren et al, 2007, 2011; Lehman et al, 2012) and their ability to modulate the immune system (Kovacsovics-Bankowski et al, 2009; Walker et al, 2010). In particular the immune-regulatory properties are of paramount importance for GvHD treatment.…”
Section: Multistem Cellsmentioning
confidence: 99%